Characterization of photomultiplier tubes in a novel operation mode for Secondary Emission Ionization Calorimetry. (6th October 2016) - Tiras, E.; Dilsiz, K.; Ogul, H.; Southwick, D.; Bilki, B.; Wetzel, J.; Nachtman, J.; Onel, Y.; Winn, D.
Abstract: Hamamatsu single anode R7761 and multi-anode R5900-00-M16 Photomultiplier Tubes have been characterized for use in a Secondary Emission (SE) Ionization Calorimetry study. SE Ionization Calorimetry is a novel technique to measure electromagnetic shower particles in extreme radiation environments. The different operation modes used in these tests were developed by modifying the conventional PMT bias circuit. These modifications were simple changes to the arrangement of the voltage dividers of the baseboard circuits. The PMTs with modified bases, referred to as operating in SE mode, are used as an SE detector module in an SE calorimeter prototype, and placed between absorber materials (Fe, Cu, Pb, W, etc.). Here, the technical design of different operation modes, as well as the characterization measurements of both SE modes and the conventional PMT mode are reported.